Radar foundations for imaging and advanced concepts - Sullivan, Roger J. 1941- (Raleigh, NC SciTech Publishing, 2004)
The book reviews developments in the following fields: radar fundamentals; radar imaging; synthetic aperture radar; SAR; STAP; air-to-air radar; bistatic radar; low-probability of intercept radar; LPI radar; weather radar; ground-penetrating radar; GPR; pulse-Doppler radar; and MTI radar.
Electronic reproduction.
Keywords: Radar; Microwaves; Synthetic aperture radar; Electronic books